Analysis of the consumption of sports supplements in elite fencers according to sex and competitive level - Mata, F. Domínguez, R.; López-Samanes, Á.; Sánchez-Gómez, A.; Jodra, P.; Sánchez-Oliver, A. J. (BMC Sports Science, Medicine and Rehabilitation, 2021)
Background The aim of this study was to analyze the consumption of sports supplements (SS) in competitive level fencers and compare differences based on sex and competitive level (international and national).